Judo match exercise intensities in the Judo weight divisions - Santos, L.; Federolf, P. A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The determination of the exercise intensities of the Judo match can be very useful for coaches and players to optimize training sessions. Thus, the goals of the current ´s study were to determine the exercise intensities of the Judo match (for the male and female divisions) and to define the type of relationship (independency or dependency) between the exercise intensities of the Judo match and the Judo weight divisions.